ADUBOS NITROGENADOS E POTÁSSICOS NA PRODUÇÃO DE POR TAENXERTOS DE UMBUZEIRO (Spondias tuberosa Arr. Cam.) - MIGUEL WANDERLEY DE ANDRADE (Revista Caatinga, 2013)
The objective of this work was to obtain informatio n about the best sources and doses of nitro- gen and potassium fertilizers for obtaining vigorou s rootstocks umbuzeiro in Northeastern Brazil. In s eparate experiments, we tested two sources of nitrogen, ure a and ammonium sulfate and five N rates (0, 350, 70 0, 1400 and 2800) mg.dm -3 , and two sources of potash fertilizer (potassium c hloride and potassium sulfate) in five doses of K20 (0, 1.800, 3.600, 5.400 and 7.200) mg. dm -3 substrate. The experimental design was in random- ized blocks in factorial 2 (sources) x 4 (doses), w ith ten treatments and four replications and ten pl ants per plot. Parameters were evaluated for the growth of seedlin gs. Doses of nitrogen and potassium applied to soi l had a negative influence in the survival of seedlings, shoot length, stem diameter and root fresh weight of seedlings.